Volcanic Rocks Diagenesis and Characteristics Analysis of Reservoir Space, Semilir Formation, Patuk, Gunung Kidul, Daerah Istimewa Yogyakarta - Patria, Aulia Agus (Departemen Teknik Geologi, 2018)
Arc-related volcanism activity in Java subduction system has been started since Eocene. This activity produces thick sequences ofvolcaniclastic rocks. Volcanic activity during Miocene in Southern Mountain marked by ancient volcanic that produced volcanic deposits that compose Semilir Formation. Outcrop in Ngoro-oro, Patuk, Gunung Kidul, Special Region of Yogyakarta, has an ideal dimension and various lithology to identify petrophysical properties such as reservoir space. This paper uses detailed stratigraphic measurement with 1:10 scale which determines the facies distribution and analytical petrography to determine the reservoir characteristics based on mineralogy, texture and diagenesis process. The results shows that the study area consist of lapilli-vitric stone, greywacke and vitric-crystal tuff. Volcanic rocks in Semilir Formation, Gunung Kidul area develop into three reservoir space types : primary pores, secondary pores and fractures pores. This formation of reservoir space went through diagenetic process consist of cooling and solidification stage and epidiagenesis stage. Cooling and solidification stage include fragmentation, crystallization, differentiation and solidification, epidiagenesis (Re-Construction) stage include weathering, leaching, fluid dissolution and tectonism. Primary pores were formed during volcanic active period and solidification period, marked by volcanic rocks with various composition, grain size and contraction fractures. Secondary pores and fractures pores formed at epidiagenesis (Re-Construction) stage, with distinct features as weathering-leaching period and burial period, marked by micro-structure, solution pores fracture along cleavage face and devitrification pores. Volcanic rocks diagenesis compelixity are the major factors that control of complexity and diversity in reservoir space types. Kaa kunci : diagenesis, volcanic rocks, porosity, semilir formation